2020
DOI: 10.1007/s00068-020-01520-z
|View full text |Cite|
|
Sign up to set email alerts
|

Increased and unjustified CT usage in paediatric C-spine clearance in a level 2 trauma centre

Abstract: Purpose Cervical spine injury after blunt trauma in children is rare but can have severe consequences. Clear protocols for diagnostic workup are, therefore, needed, but currently not available. As a step in developing such a protocol, we determined the incidence of cervical spine injury and the degree of protocol adherence at our level 2 trauma centre. Methods We analysed data from all patients aged < 16 years suspected of cervical spine injury after blunt trauma who had presented to our hospital during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Only one study demonstrated that updating their protocol increased primary CT scans (2.9%–45.8%), although CT after initial plain radiography decreased slightly (13.3%–6.7%) 25. As their protocol was only slightly updated between the 2 study periods, the authors attributed the large increase in primary CT to decreased adherence to the updated protocol, which could be due to many different factors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only one study demonstrated that updating their protocol increased primary CT scans (2.9%–45.8%), although CT after initial plain radiography decreased slightly (13.3%–6.7%) 25. As their protocol was only slightly updated between the 2 study periods, the authors attributed the large increase in primary CT to decreased adherence to the updated protocol, which could be due to many different factors.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, all protocols that included conscious patients (N=12) used XR as initial imaging; 10 of these studies always utilized XR first, whereas 2 indicated XR versus CT based on additional features, such as whether a CT head was already ordered15,16 or the patient’s age 26. Three protocols utilized different types of XR based on age, with the younger patients (below 5 years old in Arbuthnot and Mooney27 and below 8 years old in Ten Brinke et al25 and Luehmann et al28) undergoing anteroposterior (AP)/lateral films and the older patients receiving AP/lateral/odontoid films. The 2 protocols that pertained only to unconscious patients defaulted to CT as the initial imaging modality 20,21…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, these adult-specific decision-making paradigms have been shown to significantly reduce the need for imaging in patients who meet certain exclusion criteria . These criteria, despite having an overall low number of very young patients in their study cohorts, have been extrapolated to the pediatric trauma population in an attempt to reduce radiation exposure, cost, and unnecessary use of imaging studies . Limitations of this approach, in addition to the unclear applicability of these criteria in the young pediatric population, includes the variability in clinician comfort in evaluating young children .…”
Section: Introductionmentioning
confidence: 99%
“…The timely and accurate evaluation of pediatric blunt trauma is crucial for effective management and the prevention of potential complications [ 1 3 ]. Computed tomography (CT) imaging plays a pivotal role in the diagnostic process, providing detailed anatomical information and aiding in the identification of injuries [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%